Management of Changes in Liver Chemistry in Male Rats Acutely Exposed to Crude Petroleum Oil - C.O. Ujowundu, F.N. Kalu, L.A. Nwaogu, E.U. Ezeji, K.O. Igwe (Journal of Applied Pharmaceutical Science)
This Study investigated the protective effect of Gongronema latifolium supplemented diet against acute hepatotoxicity induced by crude petroleum oil on male rats. Oral exposure of rats to crude petroleum significantly decreased (P
Keywords: Hepatotoxicity,oxidative enzymes,crude oil,liver function enzymes,Gongronemalatifolium.